The Effect of Human Resource Competence, Utilization of Information Technology, Internal Control Systems, and Application of Government Accounting Standards on The Quality of Financial Reporting (Study on South Aceh Government SKPK) - Mery Sutrisna; Nadirsyah Nadirsyah; Indayani Indayani (Research Collaboration Community (RCC), 2022)
This study aims to examine the effect of human resource competence, the use of information technology, internal control systems and the application of government accounting standards on the quality of financial reporting in the South Aceh Government SKPK. The population in this study were 55 SKPK in South Aceh Regency. The entire population is the sample in this study and is called the census sample. Primary data sources are obtained from questionnaires distributed to 110 respondents. Respondents in this study were the Expenditure Treasurer and Financial Administration Officer at SKPK. The analytical method used is multiple linear regression analysis. The results of this study indicate that the competence of human resources, utilization of information technology, internal control, and SAP implementation together affect the quality of financial reporting. Furthermore, the results of the partial study show that HR competence affects the quality of financial reporting, the use of information technology affects the quality of financial reporting, internal control affects the quality of financial reporting, and the application of SAP affects the quality of financial reporting in the South Aceh Government SKPK.